2018
DOI: 10.21037/jtd.2018.05.116
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanism of post-lobectomy air leaks

Abstract: After upper lobectomy, the bullet shape of the apex of the exposed lower lobe was associated with high pleural stress, and a reduction in mechanical support by the chest wall to the visceral pleura due to initial post-op lack of chest wall confluence. It is suggested that such higher stress in the lower lobe apex explains the higher parenchymal air leak post-upper lobectomy. The pleural stress model also accounts for the higher incidence of right-sided prolonged air leak post-resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…[13][14][15] Access to the Chest During surgical access to the chest, a breach in the visceral pleura and parenchyma may occur. Radionucleide imaging studies of pneumothorax suggest that particles as small as 5-10 nm may be released, 11,[18][19][20][21][22][23] which may be more significant if the underlying lung is subjected to positive pressure in the event of inadequate exclusion. The working group; therefore, recommended interrupting ventilation and using utmost care when opening the intercostal space or inserting an initial thoracoscopic trocar.…”
Section: Lung Isolation and Patient Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Access to the Chest During surgical access to the chest, a breach in the visceral pleura and parenchyma may occur. Radionucleide imaging studies of pneumothorax suggest that particles as small as 5-10 nm may be released, 11,[18][19][20][21][22][23] which may be more significant if the underlying lung is subjected to positive pressure in the event of inadequate exclusion. The working group; therefore, recommended interrupting ventilation and using utmost care when opening the intercostal space or inserting an initial thoracoscopic trocar.…”
Section: Lung Isolation and Patient Positioningmentioning
confidence: 99%
“…The working group emphasized the importance of air leak prevention, because pleural tears and parenchymal staple lines may leak air and generate aerosol when the lung is re-expanded under positive pressure. [19][20][21][22][23] Although their efficacy is somewhat controversial, the use of tissue reinforcement and/or tissue sealants may be considered to promote staple line integrity, 18,[29][30][31] as can limiting ventilation pressures because some evidence suggests this may reduce strain on staple lines. 31,32 Nevertheless, because the potential for air leak is inherent to lung surgery, the working group suggested that lung re-expansion proceed only once the pleural cavity has been excluded from the operating room environment.…”
Section: Conduct Of the Surgical Proceduresmentioning
confidence: 99%
“…The gravitational model cannot explain lack of postural inequality in the prone position and heterogeneity of ventilation and perfusion distribution at the same vertical level with persistent heterogeneity in the absence of gravity [49]. The non-symmetrical fractal branching of the bronchial and pulmonary vascular anatomy is now considered to be the most important factor causing heterogeneity of perfusion and ventila- in the upper lobes and also on the right compared to the left due to the loss of chest wall conformational support leading to high pleural stress [75].…”
Section: Pulmonary Vasculaturementioning
confidence: 99%
“…To do so, a surgical stapler squeezes tissue around the tumor to cut and seal the healthy tissue from the tumor bearing one. After chest surgery, 28-60% of patients suffer from air leaks [1]- [4]. Patients routinely require a chest tube (drain) until the leak resorbs [2], [5], which results in longer hospital stays and increased care costs [6].…”
Section: Introductionmentioning
confidence: 99%
“…al. [1]. They concluded that lower lobes leak most because they need to reshape to fit the rib cage bullet-shape exposing them to higher mechanical stress.…”
Section: Introductionmentioning
confidence: 99%